Participatory Selection of Local Ecotypes of Voandzou by Producers in a Controlled Environment in the Sudanian Zone of Chad - Goalbaye, Touroumgaye; Ngariban, Tamtial; Daouya, Philémon; Kaboul, Brahim; Jous, Clément; Bravo, Daniel; Solo, Grace Yassi (European Journal of Applied Sciences, 2025)
The cultivation of voandzou (Vigna subterranea L) appears to be neglected ; it remains largely a traditional and family-based agriculture. Consequently, its productivity is low due to unknown technical itineraries and limited access to high-performing varieties by farmers. The objective of this study is to involve producers in evaluating the varietal characteristics of local ecotypes in a controlled environment. The plant material consists of twenty (20) local voandzou ecotypes selected across Chad’s regions and pre-coded. The « mother trial » experiment is conducted following a Fisher block experimental design with three repetitions. Participatory varietal selection (PVS) is carried out with about forty farmers. Two groups are formed for this operation : a group of fourteen (14) women and a group of fourteen (14) men. Each group received six different-colored cards to assess the best ecotypes and identify the mediocre ones. The Ts_Vou_81 variety was the most appreciated at 28.57% by men for its varietal characteristics. The second most appreciated variety by men is TS_vou_79 at 23.80%. The third is TS_vou_104 at 19.04%. Among women, Ts_vou_166 was the most appreciated at 19.04%. Varieties TS_vou_104, Ts_vou_2, and Ts_vou_79 follow, each appreciated at 14.28% by women. The varieties Ts_vou_81 and TS_vou_79 were equally appreciated at 19.51% by both men and women. The third most appreciated at 17.07% by both genders is TS_vou_104. The ecotypes that meet the satisfaction criteria of the participating breeders will be made available for dissemination.